Analysing the Effect of Microenterprise Development on Rural Households’ Savings in the Tolon District of Ghana: A Switching Regression Approach - Azumah, Shaibu Baanni; Adzawla, William; Tiweh, Augustine Logoti (Journal of Asian Business Strategy, 2015)
This paper examined the effect of microenterprise development on rural household saving in the Tolon district of Northern region of Ghana. It involved 105 farm households selected through a two-stage sampling approach. A switching regression model was fitted to correct selectivity bias problem. From the result, males; non-household heads; farmers who had access to credit; farmers with high income and farmers further from micro institution had the higher probability of engaging in microenterprise activities. Among other factors, female dependent, income level and interest rate significantly influenced the amount of money saved by the households. The study demonstrated that microenterprise development is not only necessary for safeguarding the future of rural households but also for the sustainability of financial institutions. Policy makers are encouraged to take the opportunity to enhance the existing microenterprises in the district and also introduce new lucrative ones while rural households also give microenterprise businesses the much attention. Credit facilities should be made available to the households to boost their microenterprises.